A case of aggressive aortic prosthetic valve endocarditis aggressive caused by Staphylococcus lugdunensis - Kazuhiro Yamazaki; Kenji Minakata; Kazuhisa Sakamoto; Jiro Sakai; Yujiro Ide; Masahide Kawatou; Hideo Kanemitsu; Tadashi Ikeda; Kenji Minatoya; Ryuzo Sakata (Surgical Case Reports, 2020)
Abstract Background Staphylococcus lugdunensis is a coagulase-negative Staphylococcus species, which are weak pathogenic bacteria generally. However, the acute and severe pathogenicity of Staphylococcus lugdunensis infective endocarditis may be due to the rapid growth of large vegetation and consequent valve destruction. Case presentation The patient was an 81-year-old male who visited our hospital with chief complaints of low back pain and high fever. Four years before this visit, he had undergone aortic valve replacement for aortic regurgitation. He was found to be hypotensive. Although there is no heart murmur on auscultation and echocardiography revealed negative findings with aortic valve, a blood test showed increases in the white blood cell count and C-reactive protein concentration. On the next day, Gram-positive cocci were detected in a blood culture and echocardiography detected a large vegetation on the prosthetic valve with increased flow velocity. Therefore, he underwent redo aortic valve replacement emergently. Staphylococcus lugdunensis was identified in blood samples and vegetation culture. Consequently, the patient was treated with antibiotics for 5 weeks after the operation and discharged home. Conclusions We experienced rapidly progressive prosthetic valve endocarditis caused by Staphylococcus lugdunensis. Hence, Staphylococcus lugdunensis infective endocarditis requires aggressive treatment, and the pathogenicity of this coagulase-negative Staphylococcus with high drug susceptibility should not be underestimated.